Affective Commitment in Islamic Philanthropic Organizations in Indonesia: The Impact of Workplace Spirituality and Islamic-Based Organizational Culture - Rhienta Aprisella; Fuad Mas'ud (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to analyze the impact of Islamic spirituality and Islamic-based organizational culture on employee affective commitment in the context of Islamic philanthropic organizations in Indonesia. This research method uses a quantitative approach with data collection through online questionnaires. Multiple linear regression analysis techniques were used to identify the relationship between variables of Islamic spirituality in the workplace, Islamic organizational culture, and affective commitment. The total research sample amounted to 135 employees from 12 Islamic philanthropic organizations in Indonesia. From these findings, it can be concluded that Islamic philanthropic organizations in Indonesia can strengthen employees' affective commitment by considering the application of Islamic spiritual values in the workplace and building an organizational culture that is in accordance with Islamic principles. By creating a work environment that supports both of these factors, organizations can foster stronger emotional bonds between employees and the organization and advance their philanthropic goals more effectively.